2005
DOI: 10.1103/physrevb.71.155210
|View full text |Cite
|
Sign up to set email alerts
|

Interacting quantum rotors in oxygen-doped germanium

Abstract: We investigate the interaction effect between oxygen impurities in crystalline germanium on the basis of a quantum rotor model. The dipolar interaction of nearby oxygen impurities engenders nontrivial low-lying excitations, giving rise to anomalous behaviors for oxygen-doped germanium ͑Ge:O͒ below a few degrees Kelvin. In particular, it is theoretically predicted that Ge:O samples with oxygen-concentration of 10 17-18 cm −3show ͑i͒ power-law specific heats below 0.1 K, and ͑ii͒ a peculiar hump in dielectric su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, the existing data are in severe contradiction with each other, and not yet settled down to a reliable precision for test of charge symmetry. In addition Shima et al [3] remeasured the photodisintegration of 4 He and reported that the cross section monotonically increases with the excitation energy up to £ r =32 MeV, and no pronounced peak of the GDR was observed at around E 7 =25 MeV. It is much higher than the previously adopted value of 25 MeV.…”
mentioning
confidence: 91%
“…However, the existing data are in severe contradiction with each other, and not yet settled down to a reliable precision for test of charge symmetry. In addition Shima et al [3] remeasured the photodisintegration of 4 He and reported that the cross section monotonically increases with the excitation energy up to £ r =32 MeV, and no pronounced peak of the GDR was observed at around E 7 =25 MeV. It is much higher than the previously adopted value of 25 MeV.…”
mentioning
confidence: 91%
“…Two-dimensional rotational manner has been observed in the experiments of hydrogen on a surface [18][19][20]. The planar rotation in diverse configurations * yyliao@nuk.edu.tw further leads to interesting consequences for energy spectrum [21,22], molecular orientation [23], and specific heat [24,25]. In this work we study the entanglement in a system of two polar molecules confined to a plane.…”
Section: Introductionmentioning
confidence: 99%
“…This configuration acts as a new hindering potential in addition to the four-fold inversion symmetric potential V h . This argument can be straightforwardly extended to the case of multiple pairs providing many potential minima in the configuration space P = (θ 1 , θ 2 , θ 3 , • • •) [23], where the potential function is…”
mentioning
confidence: 99%